2011
DOI: 10.7863/jum.2011.30.4.463
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Sonogram

Abstract: With a slight reduction in the Down syndrome detection rate, the use of the likelihood ratio approach was associated with a significantly lower false-positive rate compared with the logistic regression approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Another example is showed by Moreno-Cid et al, who performed a systematic review of the clinical prediction rules for the risk of Down syndrome based on ultrasound findings in pregnancy [31]. These authors showed that only 3 of the rules were validated (2 internally and 1 externally) and 4 of them were incorporated into a software application [32-35]. Moreover, a recent systematic review evaluated Web-based cardiovascular disease risk calculators in terms of clinical validity, understandability, and actionability [36].…”
Section: Discussionmentioning
confidence: 99%
“…Another example is showed by Moreno-Cid et al, who performed a systematic review of the clinical prediction rules for the risk of Down syndrome based on ultrasound findings in pregnancy [31]. These authors showed that only 3 of the rules were validated (2 internally and 1 externally) and 4 of them were incorporated into a software application [32-35]. Moreover, a recent systematic review evaluated Web-based cardiovascular disease risk calculators in terms of clinical validity, understandability, and actionability [36].…”
Section: Discussionmentioning
confidence: 99%
“…The present study by Verlohren and colleagues nicely demonstrates that an increase in this ratio before thirty-four weeks of gestation has high sensitivity and specificity to predict the occurrence of preeclampsia in their European cohort; 95% and 94% respectively for a cut-off of 33. However, sFlt-1/PlGF ratios after 34 weeks in preeclamptic pregnancies are not as informative because of the increase in these ratios during uncomplicated pregnancy (4,5,7). Moreover, the similarities of values in late onset preeclampsia to those in uncomplicated pregnancies suggest that alternative or parallel pathways other than angiogenic balance may contribute to hypertension in late-onset preeclampsia.…”
mentioning
confidence: 99%
“…In discussion of limitations, Verlohren et al note that they did not calculate positive or negative predictive values directly from their data set due to the study design. However, one can combine an overall PE rate of 2–5% and the distributions of sFlt-1/PlGF for preeclampsia and non- preeclamptic pregnancies to derive risks of preeclampsia for given gestational ages as well as positive or negative predictive values (7). In addition, other risk factors or recently identified biomarkers in blood or urine such as complement products C3a, C5a, C5b-9, angiotensin type 1 receptor auto-antibodies, or the insulin like growth factor acid labile subunit should also be tested in models to refine this approach (3;8;9).…”
mentioning
confidence: 99%